Thermal performance in square-duct heat exchanger with quadruple V-finned twisted tapes - Promvonge, Pongjet (My University, 2015)
An investigation on heat transfer augmentation in a square duct with insertion of combined 30°V-fins and quadruple counter-twisted tapes is conducted experimentally. Air as the working fluid enters the test duct having a uniform wall heat-flux condition with Reynolds number ranging from 4000 to 30,000 in the present work. The combined vortex generators (called "V-finned counter-twisted tape") are obtained by incorporating V-fins into the edges of quadruple twisted-tapes having a similar twist ratio of 4. The effect of pertinent V-fin parameters such as four relative fin height, (RB = e/w = 0.16, 0.21, 0.32 and 0.42) and relative fin pitch, (RP = P/w = 4, 8, 12 and 16) at a single fin attack angle, α = 30°on thermal characteristics is examined. The experimental results reveal that the heat transfer and pressure drop in the form of respective Nusselt number and friction factor from the V-finned counter-twisted tape tend to increase with the rise of RB but show the reversing trend with increasing RP. The thermal performance of the V-finned counter-twisted tape is considerably higher than that of the quadruple twisted tapes alone. The V-finned counter-twisted tape with RB = 0.42 and RP = 4 yields the maximum Nusselt number and friction factor but the one with RB = 0.21 and RP = 4 provides the highest thermal performance of about 1.75 at lower Reynolds number.
Keywords: Fin; Friction factor; Heat transfer; Square-duct heat exchanger; Twisted-tape